Business intelligence applications on household expenditure survey of 2016 and 2019 - Serah Lathan Sathiamoorthi,; Siti Noor Asyikin Mohd Razali,; Muhammad Ammar Shafi,; Rosshairy Abd Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2023)
According to The Malaysia Reserve, following the implementation of the new RM1,500 minimum wage, prices of basic items in the country will likely rise by 50 percent to 60 percent beginning in June. This will affect the manufacturing cost. Due to increased manufacturing costs and inflation, beverage firms have been under a great deal of pressure to boost their pricing. This will impact the Malaysian household expenditure. The spending of consumer will increase drastically. Therefore, a proper study must be conducted on the expenditures among Malaysian people to understand the trend and current statistics of various races, income, occupation, and education level. In this research, descriptive analysis, tree decomposition method, and scatter plot clustering has been applied to examine household expenditure. Microsoft Power Business Intelligence (Power BI) has been applied as a tool to visualize the statistic, pattern or trends that could be explored through an attractive dashboard. The dashboard represents the monthly expenditure averages by state, marital status, strata, and gender. In addition, average total income and expenditures by occupation, ethnicity, highest level of education, and industry also presented that could be explored by user in detail. Result shows that the income and expenditures in Malaysia have been increased from 2016 to 2019. According to the ethnicity, Chinese concur the highest monthly expenses in both 2016 and 2019 compared to other races. Meanwhile based on industry, activities of household as employers has the highest expenses and occupation as a manager is also represents the highest income as well as highest monthly expenses. Furthermore, based on education level, Malaysian people who studied until degree and above has highest average income and expenses monthly. Future works could be done by analyzing factors that affect the increases of expenses among Malaysian people.